Cyanobacterial Pigments as Natural Anti-Hyperglycemic Agents: An In vitro Study - Ghosh, Tonmoy; Bhayani, Khushbu; Paliwal, Chetan; Maurya, Rahulkumar; Chokshi, Kaumeel; Pancha, Imran; Mishra, Sandhya (Frontiers in Marine Science, 2016)
Traditional medicines for controlling postprandial hyperglycemia includes herbs and plant extracts as well as synthetic drugs like acarbose. Synthetic drug molecules frequently have side effects such as flatulence and diarrhea. Cyanobacterial pigments have excellent anti-oxidant and free radical scavenging properties. Thus, α-amylase and α-glucosidase inhibiting activities of purified pigments and crude extracts from three cyanobacterial species, Lyngbya, Microcoleus, and Synechocystis sp., were investigated. Lyngbya extract had the highest total anti-oxidant activity (TAC) before digestion (48.26 ± 0.04 μg AAE ml−1) while purified lycopene had the highest TAC after digestion (154.16 ± 0.96 μg AAE ml−1). The Microcoleus extract had the highest ABTS scavenging activity before digestion (98.23 ± 0.25%) while purified C-phycocyanin (C-PC) had the highest ABTS scavenging after digestion (99.69 ± 0.04%). None of the digested or undigested extracts performed better than acarbose in inhibiting α-amylase but the digested Microcoleus extract was able to inhibit its activity by 35%. The purified pigments gave inhibitory activities ranging from 8 to 16%. The Lyngbya extract had the highest inhibitory activity against α-glucosidase both before and after digestion (62.22 ± 0.02 and 97.82 ± 0.03%, respectively). Purified C-phycoerythrin (C-PE), C-PC, lycopene and myxoxanthophyll could inhibit α-glucosidase in a range of 83–96%. Considering the potent inhibitory activities of purified pigments against both α-amylase and α-glucosidase, cyanobacterial pigments could be used as food additives for their dual advantage of anti-oxidant and anti-hyperglycemic activities.